The effect of electricity reliability on the sustainability of SMEs in Fako Division of Cameroon - Tapang, Felix; Mbarika, Irene (Annals of Human Resource Management Research, 2023)
Purpose: To investigate the effects of the reliability of electricity supply on the sustainability of SMEs in Cameroon. Research Methodology: This study investigates the effects of the reliability of electricity supply on the sustainability of SMEs in Cameroon. The study used a quantitative approach with the philosophical underpinnings of objectivist ontology and positivist epistemology. Primary data were obtained through closed-ended questionnaires that were responded to by 54 purposively sampled participants in the Fako division. The data were analyzed by Structural Equation Modeling (SEM) using SPSS 23 and SPSS Amos 24 software. Results: The study revealed that sporadic electricity supply interruptions, chronic electricity supply interruptions, and momentary electricity supply interruptions have no significant positive impact on the sustainability of SMEs in the Fako Division of the Southwest Region of Cameroon. Limitations: This study had a limitation in methodology, as it used a quantitative approach only. A better understanding of this study’s phenomenon can be achieved by adopting a mixed research method, where the qualitative aspect will provide a deeper understanding of the effects of other variables that affect  SME sustainability. Contribution: Based on the results of this study, business managers will come to the understanding that the sustainability of their businesses is not dependent on the reliability of the electricity supply. This means that other variables responsible for the sustainability of businesses can be studied qualitatively.